Ecology of Veliidae and Mesoveliidae (Heteroptera: Gerromorpha)in Central Europe - Ditrich, Tomáš (Jihočeská univerzita, 2011)
Ecology of Veliidae and Mesoveliidae (Hemiptera: Heteroptera: Gerromorpha) was studied in selected European species. The research of these non-gerrid semiaquatic bugs was especially focused on voltinism, overwintering with physiological consequences and wing polymorphism with dispersal pattern. Hypotheses based on data from field surveys were tested by laboratory, mesocosm and field experiments. New data on life history traits and their ecophysiological consequences are discussed in seven original research papers (four published journal papers, two submitted papers and one communication in conference proceedings), creating core of this thesis.
Ecology of Veliidae and Mesoveliidae (Heteroptera: Gerromorpha)in Central Europe
Keywords: Insects; semiaquatic bugs; life history; overwintering; voltinism; dispersion; wing polymorphism; Insects; semiaquatic bugs; life history; overwintering; voltinism; dispersion; wing polymorphism